1993
DOI: 10.1164/ajrccm/148.1.145
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Short-term Administration of Aerosolized Recombinant Human Deoxyribonuclease in Patients with Cystic Fibrosis

Abstract: Chronic endobronchial bacterial infection evokes purulent airway secretions in patients with CF. The viscoelastic properties of these secretions is primarily due to the presence of polymerized DNA from degenerating leukocytes. Recombinant human DNase I (rhDNase) reduces the viscosity of CF sputum in vitro. To test the hypothesis that rhDNase would improve pulmonary function in children and adults with CF, we compared the efficacy and safety of 10-day administration of three doses of aerosolized rhDNase (0.6, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
100
1
5

Year Published

1997
1997
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(108 citation statements)
references
References 21 publications
2
100
1
5
Order By: Relevance
“…The current study aimed to assess the medium-term safety and tolerability of moderately high dose inhaled unfractionated heparin in CF adults and to explore possible in vivo mucolytic (assessed by lung function, symptom scores and quality of life) and anti-inflammatory outcomes. The study was powered to detect a 10% improvement in forced expiratory volume in one second (FEV1) as a result of enhanced sputum clearance, consistent with the short-term effect demonstrated in early studies of DNase [25].…”
mentioning
confidence: 58%
“…The current study aimed to assess the medium-term safety and tolerability of moderately high dose inhaled unfractionated heparin in CF adults and to explore possible in vivo mucolytic (assessed by lung function, symptom scores and quality of life) and anti-inflammatory outcomes. The study was powered to detect a 10% improvement in forced expiratory volume in one second (FEV1) as a result of enhanced sputum clearance, consistent with the short-term effect demonstrated in early studies of DNase [25].…”
mentioning
confidence: 58%
“…RhDNAse treatment in CF has been shown to be effective, improving lung function and decreasing the number of respiratory exacerbations [11][12][13][14][15][16][17][18][19]. The exact reason for this positive effect remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…RhDNAse breaks down extra cellular DNA, thereby decreasing the viscosity of sputum. Several long term clinical trials showed that rhDNAse treatment is effective, especially in mild to moderate CF, shown by an increase in lung function and a decrease of respiratory exacerbations [10][11][12][13][14][15][16][17][18][19]. A study preformed in Denmark hypothesized that this clinical improvement in lung function might be due to a decrease in bacterial airway colonization [11].…”
Section: Introductionmentioning
confidence: 99%
“…Improvements in lung function have also been documented [157,158] . Viscosity is decrease d by enzymatic degradation of host and bacterial DNA, with the added advantage that TLR9-mediated signalling in response to uCpG DNA is likely to be abrogated also.…”
Section: Mucolytic Therapiesmentioning
confidence: 90%